2018
DOI: 10.1016/j.celrep.2018.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR/Cas9 Screen Identifies Host Factors Essential for Influenza Virus Replication

Abstract: SUMMARY The emergence of influenza A viruses (IAVs) from zoonotic reservoirs poses a great threat to human health. As seasonal vaccines are ineffective against zoonotic strains, and newly transmitted viruses can quickly acquire drug resistance, there remains a need for host-directed therapeutics against IAVs. Here, we performed a genome-scale CRISPR/Cas9 knockout screen in human lung epithelial cells with a human isolate of an avian H5N1 strain. Several genes involved in sialic acid biosynthesis and related gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
196
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(205 citation statements)
references
References 49 publications
9
196
0
Order By: Relevance
“…RNAi has enabled systematic exploration of host genes involved in virus replication and virulence, thereby allowing identification of novel drug targets (Radoshitzky et al, 2016). Since the last decade, a large number of genome-scale RNAi screens have been conducted, which identified cellular factors required for WNV (Krishnan et al, 2008), DENV (Morchang et al, 2017;Sessions et al, 2009), HIV-1 (Zhou et al, 2008), HCV Lupberger et al, 2015;Tai et al, 2009), IAV (Han et al, 2018;Karlas et al, 2010), JUNV (Lavanya et al, 2013), coronavirus (Staff, 2015), poxvirus (Kilcher et al, 2014), herpesvirus (Griffiths et al, 2013) and polyomavirus (Zhao and Imperiale, 2017) replication. siRNA screens reveal both proviral and antiviral cellular factors and therefore help in understanding the precise nature of virus-host interactions .…”
Section: Genome-wide Sirna Screens To Identify Cellular Factors Requimentioning
confidence: 99%
“…RNAi has enabled systematic exploration of host genes involved in virus replication and virulence, thereby allowing identification of novel drug targets (Radoshitzky et al, 2016). Since the last decade, a large number of genome-scale RNAi screens have been conducted, which identified cellular factors required for WNV (Krishnan et al, 2008), DENV (Morchang et al, 2017;Sessions et al, 2009), HIV-1 (Zhou et al, 2008), HCV Lupberger et al, 2015;Tai et al, 2009), IAV (Han et al, 2018;Karlas et al, 2010), JUNV (Lavanya et al, 2013), coronavirus (Staff, 2015), poxvirus (Kilcher et al, 2014), herpesvirus (Griffiths et al, 2013) and polyomavirus (Zhao and Imperiale, 2017) replication. siRNA screens reveal both proviral and antiviral cellular factors and therefore help in understanding the precise nature of virus-host interactions .…”
Section: Genome-wide Sirna Screens To Identify Cellular Factors Requimentioning
confidence: 99%
“…Interestingly, further evidence exists in recent studies that utilized genome-wide siRNA knockdown or CRISPR/Cas9 knockout screens on the potential pro-viral roles of TRIMs (e.g. TRIM23) [181]. This study does not mark the first instance of TRIM23 being identified in a screen as a pro-viral factor as the NS5 component of yellow fever virus (YFV) was found to require K63-linked polyubiquitin from TRIM23 in order to interact with STAT2 and inhibit IFN-I signalling [182].…”
Section: Novel Pro-viral Roles Of Trims and Other E3 Ubiquitin Ligasesmentioning
confidence: 99%
“…5,7 On the contrary, several genome-wide screens have identified host factors essential for influenza virus replication. [8][9][10] As an alternative to the aforementioned pathogen-targeted antivirals, growing efforts are devoted to blocking or promoting host factors to fight influenza viruses. 11 By modulating host factors involved in viral replications, these host-targeted antiviral strategies may be less susceptible to strain variations and mutations as they do not exert a selective pressure on the target pathogen.…”
Section: Introductionmentioning
confidence: 99%